A systematic review of the effectiveness of alcohol brief interventions for the UK military personnel moving back to civilian life. Issue 4 (20th March 2017) - Wigham, Sarah; Bauer, A; Robalino, S; Ferguson, J; Burke, A; Newbury-Birch, D
Abstract : Background: Higher levels of alcohol consumption have been observed in the UK armed forces compared with the general population. For some, this may increase the risk of using alcohol as a coping strategy when adjusting to multiple life events occurring when moving back into civilian life. Method: A systematic review was conducted to determine the effectiveness of alcohol brief interventions for military personnel during transition. Electronic databases including Medline, Central, Healthcare Management Information Consortium (HMIC) and Embase, and grey literature, were searched. Two reviewers independently assessed potential studies for inclusion, extracted data and assessed quality of selected articles using an established instrument. Results: Ten studies met criteria for inclusion. Studies were synthesised narratively. Interventions were heterogeneous, and bias within studies may have acted to increase or decrease their reported effectiveness. The findings suggest some evidence for effectiveness of self-administered web-based interventions, involving personalised feedback over a number of sessions, and system-level electronic clinical reminders. All studies were from the USA. Delivery of interventions by a clinician during motivational interviews was most effective for those with post-traumatic stress disorder symptoms. Conclusions: A UK trial of web-based interventions with personalised feedback is recommended.